Secrets and their biographical meanings as the base for identity formation process - Karkowska, Magda; Agnieszka Gralak (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
This article discusses the importance of existing secrets in the process of identity formation. The first part presents some key notions as well as the relationships between them. They are following : private, public, individual and collective, secret and mystery as well as freedom and autonomy. The second part of the text discusses the philosophical and psychological background of the mysteries. Most important factors for the task of describing biographical importance of secrets seem to be: the design of identity, its status as well as other key concepts such as model or function seen from the development perspective.First and foremost most important in identity formation appears to be the phase of life in which the secret occurs and in which we make decisions about how to treat it. At the theoretical level it is not possible to give a clear answer to the question of specifical factors` importance.We have to take into account the status of identity, social circumstances and the environment (family, occupational) which determine the biographical importance of secrecy. It is a singular question, strongly marked by uniqueness, and to some extent also by the metaphysical element.